PENERAPAN 12 TAHAPAN HAZARD ANALYSIS AND CRITICAL CONTROL POINT (HACCP) SEBAGAI SISTEM KEAMANAN PANGAN PADA PRODUK UDANG (PANKO EBI) [The Twelve Stage Implementation of The Hazard Analysis and Critical Control Point (HACCP) as Food Safety System on The Fishery Products (Panko Ebi)] - Sutrisno Adi Prayitno; M. Bambang Sigit S (Jurnal Teknologi & Industri Hasil Pertanian, 2019)
To produce a quality product and to keep food safety, a producer needs to imple-ment the management system known as HACCP (Hazard Analysis and Critical Control Point). The purpose of the study was to evaluate the application of HACCP at Fishery Company producing frozen shrimp wrapped in bread (Panko ebi) located in the Central Java province. The data were obtained by observation, interview and active participation in all activities based on the company’s operational guide book and examined based on the principle of HACCP. The results of the study show that the CCP was at the incoming raw materials and checking of metal stages. Based on observations and verification, gen-erally this producer has well implemented the twelve stages of the HACCP to maintain quality and safety of the products.